Quality control of injectable artesunate marketed in Kisangani in the Democratic Republic of the Congo - TWENI BARUTI, Emile; Mbinze Kindenge, Jérémie; Mwanga Maombi, Jordan; Shabani Mitongo, Luc; Kadima Ntokamunda, Justin; Marini Djang’eing’a, Roland (Orapuh Journal, 2025)
Introduction Malaria remains a major public health problem in the Democratic Republic of Congo (DRC), where injectable artesunate is the standard treatment for severe forms. Effective treatment relies on the availability of high-quality medicines, including injectable artesunate. However, the circulation of falsified or substandard products poses a serious threat to patient care. Purpose This study aimed to evaluate the physicochemical quality of injectable artesunates marketed in Kisangani, based on the standards of the International Pharmacopoeia (2022) and the British Pharmacopoeia (2024). Methods A prospective qualitative and quantitative study was conducted from February to May 2024, involving 30 batches of injectable artesunate collected from pharmacies across the six municipalities of Kisangani. Analyses were carried out at the LACOMEDA laboratory in Kinshasa using the following analytical techniques: mass uniformity, pH determination, and High-Performance Liquid Chromatography (HPLC) for identification and assay of the active ingredient and impurities, in line with the pharmacopoeial standards. Results All 30 samples met the visual inspection and labelling requirements. The pH ranged from 3.62 to 4.23, while mass uniformity was within ±10%, consistent with the British Pharmacopoeia (2024). Artesunate content ranged from 95.9% to 108.1%, within the specified limits (90–110%). Impurities A, B, and C were detected in low amounts; impurity A ranged from 0.2% to 0.7%. All impurity levels remained below the acceptance thresholds defined by the International Pharmacopoeia (2022). Conclusion All analysed samples complied with pharmacopoeial specifications during the study period. These results underscore the importance of systematic post-marketing surveillance to prevent the distribution of substandard drugs in pharmacies in Kisangani, DRC.